2007
DOI: 10.1186/1471-2164-8-237
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome expression profiling reveals a significant role for immune function in human abdominal aortic aneurysms

Abstract: Background: Abdominal aortic aneurysms are a common disorder with an incompletely understood etiology. We used Illumina and Affymetrix microarray platforms to generate global gene expression profiles for both aneurysmal (AAA) and non-aneurysmal abdominal aorta, and identified genes that were significantly differentially expressed between cases and controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
240
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(267 citation statements)
references
References 62 publications
(60 reference statements)
25
240
0
Order By: Relevance
“…41 Moreover, the expression of TEAD3 and TEAD4 are both suppressed in the wall of the aorta of aortic aneurysm patients compared to healthy controls. 42 Thus, these TEAD factors were strong candidates for mediating TGF-β-dependent gene expression at the 9p21.3 locus in HAoSMCs. TGF-β is known to induce p16 and p15 expression to mediate cellular senescence and control cellular proliferation.…”
Section: Discussionmentioning
confidence: 93%
“…41 Moreover, the expression of TEAD3 and TEAD4 are both suppressed in the wall of the aorta of aortic aneurysm patients compared to healthy controls. 42 Thus, these TEAD factors were strong candidates for mediating TGF-β-dependent gene expression at the 9p21.3 locus in HAoSMCs. TGF-β is known to induce p16 and p15 expression to mediate cellular senescence and control cellular proliferation.…”
Section: Discussionmentioning
confidence: 93%
“…Analyzing the results of such profiles generated for AAA tissues showed an overrepresentation of biological pathways involved in immune response, 84 providing further evidence that AAA is an immunologic disease.…”
Section: Global Gene Expression Profiles Of Aaa Tissue Reveal a Signimentioning
confidence: 87%
“…Lenk et al 40 demonstrated that regulation of the actin cytoskeleton, focal adhesion, ECM-receptor, immune response, and inflammatory pathways was involved in the pathogenesis of AAAs. Cell communication has also been previously linked to the pathogenesis of AAAs.…”
Section: Shi Et Al Genomics Of Human Intracranial Aneurysmsmentioning
confidence: 99%